(NlITERATURNYE WOSPOMINANIQ (B:s (Ns PRILOVENIEM POLNOGO TEKSTA WOSPOMINANIJ p(B.(Nm(B. (NkOWALEWSKOGO (B/s - (NgRIGOROWI^(B, (NdMITRIJ wASILXEWI^s 1815-1876; (NkOMAROWI^(B, (Nw(B.(Nl(B.s ((NlENINGRAD (B:s Academia, 1928)
(NsODERV(B. (NPRILOVENIE (B: (Ne(B.(Na(B. (N{TAKEN[NEJDER (B"(NiZ DNEWNIKA(B" ; (NaLEKSANDR d@MA (B((NOTEC(B) "(NwPE^ATLENIQ OT POEZDKI W rOSSI@(B"((NGLAWY (BXXXVII, XXXVIII) ; (Ni(B.(Ni(B. (NpANAEW (B"(NpETERBURGSKAQ VIZNX(B"s
Keywords: (NrUSSKAQ LITERATURA (B19 (NWEKAs -- (NwOSPOMINANIQs